2018
DOI: 10.1016/j.envsoft.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Including robustness considerations in the search phase of Many-Objective Robust Decision Making

Abstract: Highlights • MORDM aims at developing robust solutions but identifies them only under a reference scenario. • We propose an extension to the search phase of MORDM. • We generate the candidate solutions under multiple scenarios. • We select these scenarios based on diversity and policy relevance. • We obtain a wider variety of robustness tradeoffs compared to the reference case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…This signified the importance of focusing on robustness rather than optimality in decision support when uncertainty exists, also emphasised in the literature (see e.g. (Eker & Kwakkel 2018;Hamarat et al 2014;Moallemi, Elsawah & Ryan 2018)). Given the benefits and drawbacks of each approach, we acknowledge that both approaches can benefit the decision maker in different under different conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This signified the importance of focusing on robustness rather than optimality in decision support when uncertainty exists, also emphasised in the literature (see e.g. (Eker & Kwakkel 2018;Hamarat et al 2014;Moallemi, Elsawah & Ryan 2018)). Given the benefits and drawbacks of each approach, we acknowledge that both approaches can benefit the decision maker in different under different conditions.…”
Section: Discussionmentioning
confidence: 93%
“…decision and scenario) is valid. Several examples of the use of robust optimisation in robust decision support frameworks can be found in previous studies (Eker & Kwakkel 2018;Herman et al 2015;Moallemi et al 2018;Moallemi, Elsawah & Ryan 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many-objective robust decision making (MORDM; Kasprzyk et al, 2013) extends the exploratory modeling concepts by including multi-objective evolutionary optimization to discover candidate actions and characterize how their vulnerabilities and trade-offs vary across deeply uncertain futures. More recently, several studies (Eker & Kwakkel, 2018;Trindade et al, 2017;Watson & Kasprzyk, 2017) have demonstrated that the inclusion of deep uncertainties in the search phase of the MORDM framework can improve solutions' robustness and discovered performance trade-offs between conflicting objectives.…”
Section: Research Articlementioning
confidence: 99%
“…We provided a proof of principle implementation by adapting ε-NSGAII (Kollat & Reed, 2006). The MOEA approach enables easy extensions by bringing in additional scenario relevant considerations such as diversity and consistency (Carlsen, Lempert, Wikman-Svahn, & Schweizer, 2016;Eker & Kwakkel, 2018). Within an MOEA framework, these can easily be added as additional objectives, rather than be calculated in postprocessing as with PRIM.…”
Section: Con Clus Ionmentioning
confidence: 99%